Performance Evaluation of Propagation Model in DVB-T2 Broadcasting: Case Study in Kebumen - Cici Tri Eviana; Siti Zulaecha; Ganang Tulus Prananda; Solichah Larasati; Muhammad Panji Kusuma Praja (LPPM Universitas Negeri Semarang, 2026)
The widespread change from analog to digital television broadcasting in Indonesia has led to the emergence of blank spots in some areas. To overcome this problem, an optimal propagation model is needed to improve transmitter coverage, energy efficiency, and field strength through optimal transmit power for DVB-T2 broadcasts. This research addresses the selection and analysis of an appropriate propagation model, focusing on the application of the Longley-Rice and ITU-R.P 1546-6 models in the Kebumen region of Central Java, Indonesia. This study specifically compares the two models to determine the most effective model in reducing blank spots in the area. The results show that the Longley-Rice model produces greater field strength than the ITU-R.P 1546-6 model. In addition, this study also found that the farther the receiver is from the transmitter, the higher the free space loss value. This is because due to the hilly geographical conditions in the Kebumen area, it causes high loss. And the farther the receiver is from the transmitter and the greater the frequency value, the greater the field strength value. This research not only provides relevant empirical data for the Kebumen region but also offers insights that can be used in the optimization of digital broadcasting in other urban environments in the future.